Examination of Social Studies-Based Curricula in Terms of Social Skills: A Comparative Investigation of Education Culture in Canada and Turkey - Ütkür Güllühan, Nur; Bekiroğlu, Derya (Journal of History Culture and Art Research, 2022)
This study aims to comparatively examine the types of social skills in the outcomes of Social Studies curriculum of Canada (Ontario) and Life Studies and Social Studies curriculum of Turkey. The study was conducted by a qualitative method. In the study, data was collected by document review. Descriptive analysis was used for the data analysis. According to the findings, despite there are differences in the frequency of social skills in Canada’s Social Studies curriculum and Life studies and Social Studies curricula of Turkey; The types of social skills that stand out in primary school 1st and 2nd-grade outcomes of both countries are similar. It was found that the most frequently used social skill types in primary school 1st and 2nd-grade curriculum outcomes are "initial and advanced social skills." Also, the most frequently used social skill types in the curriculum of both countries in the 3rd and 4th-grade outcomes are "planning skills." The skills of dealing with feelings were not in the 3rd-grade outcomes of Canada Social studies curricula; the skills of coping with stress were not in the 3rd-grade outcomes of Turkey. As a result, the social studies curricula of both countries are acceptable in terms of "initial, advanced social skills, and planning skills".